GC-MS vs. GC-MS-MS analysis of pentacyclic terpanes in crude oils from Libya and Serbia - a comparison of two methods - Faraj Musbah Abduljalil M.; Šolević-Knudsen Tatjana; Stojanović Ksenija; Ivković-Pavlović Sonja; Nytoft Hans Peter; Jovančićević Branimir (Journal of the Serbian Chemical Society, 2017)
The values of parameters calculated from distribution and abundance of the selected pentacyclic terpanes in crude oils from Libya and Serbia, which were originally derived from gas chromatography-mass spectrometry (GC–MS) were compared with results of quantification based on gas chromatography– –mass spectrometry-mass spectrometry (GC–MS-MS). The parameters analyzed are the most often used terpane source and maturity parameters, which were applied to a large sample set of 70 oils, originating from five oil fields. The aim of the paper was to investigate to which extent the measurements of the selected parameters by these two instrumental techniques agree and to determine the influence of differences between parameter values on geochemical interpretation. For that purpose two methods, concordance correlation coefficient and mean-difference plot were used. The obtained results indicate that calculation of C2718α(H)-22,29,30-trisnorneohopane/(C2718α(H)-22,29,30- -trisnorneohopane + C2717α(H)-22,29,30-trisnorhopane), C2918α(H)-30-norneohopane/ C2917α(H)21β(H)-30-norhopane and C2917α(H)21β(H)-30-norhopane/ C3017α(H)21β(H)-hopane ratios either by GC–MS or GC–MS-MS do not significantly influence interpretation. On the other hand, the determination of C3017β(H)21α(H)-moretane/C3017α(H)21β(H)-hopane ratio, gammacerane index and oleanane index by GC–MS vs. GC-MS-MS could notably affect interpretation. These differences can be explained by the co-elution and the peak overlapping in GC–MS but also by better separation, higher precision and better selectivity of the GC–MS-MS. Deviation of the almost all studied parameters from the line of equality was similar for the oils from the same oil field but some differences were observed for the oils from different oil fields. Therefore, when GC–MS-MS results are to be used in organic geochemical interpretations, a regional calibration of GC–MS vs. GC-MS-MS relationship for each petroleum system is highly recommended. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 176006]